Sistem Informasi Simpan Pinjam pada Koperasi Simpan Pinjam Hangoluan Medan - Sinaga, Yolanda Yastasia; Saragih, Rijois Iboy E.; Purba, Eviyanti Novita (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
The rapid development of information technology makes the need for various information increasing. The need for an information system is needed so that the processing of data contained in cooperatives can be more effective and accurate. Savings and loan cooperatives are institutions engaged in finance with business activities in the form of receiving deposits and loans. This is intended to help improve the welfare of the Indonesian people. The author tries to make a Final Project regarding the cooperative savings and loan program which until now has not been computerized or is still done manually. The system, which is still done manually, allows errors in recording, inaccurate reports made, and delays in finding the necessary data. Member registration, storage, loan application, and loan installment payments where all of that can be done more quickly and accurately by making an application that is poured in the form of a web. This information system is created  using the Sublime Text  3 application, while the programming language uses PHP, to run a web server using XAMPP, and MySQL is used for database management. With this information system, it is expected to make it easier for the community and cooperative members to get savings and loans information at the Hangoluan Medan Savings and Loans Cooperative.